Miniature optical fiber accelerometer based on an in-situ 3D microprinted ferrule-top Fabry–Pérot microinterferometer - Peng Wang; Taige Li; Htein Lin; Pengcheng Zhao; Shangming Liu; Hwa-Yaw Tam; A. Ping Zhang (Light: Advanced Manufacturing)
Accelerometers are crucial sensors that measure acceleration resulting from motion or vibration. Compared with their electromechanical counterparts, optical accelerometers are widely regarded as the most promising technology for high-requirement applications. However, compact integration of various optical and mechanical components to create a miniature optomechanical microsystem for acceleration sensing remains a challenge. In this study, we present a miniature optical fiber accelerometer based on a 3D microprinted ferrule-top Fabry–Pérot (FP) microinterferometer. In-situ 3D microprinting technology was developed to directly print a sub-millimeter-scale 3D proof mass/thin-film reflector-integrated FP microinterferometer on the inherently light-coupled end face of a fiber optic ferrule. Experimental results demonstrate that the optical fiber accelerometer has a flat response over a bandwidth of 2 to 3 kHz and its noise equivalent acceleration is 62.45 μg/Hz under 1-g acceleration at 2 kHz. This ultracompact optical fiber interferometric accelerometer offers several distinct advantages, including immunity to electromagnetic interference, remote-sensing capability, and high customizability, making it highly promising for a variety of stringent acceleration-monitoring applications.